2015
DOI: 10.1021/jf504715p
|View full text |Cite
|
Sign up to set email alerts
|

Protein Precipitation Behavior of Condensed Tannins from Lotus pedunculatus and Trifolium repens with Different Mean Degrees of Polymerization

Abstract: The precipitation of bovine serum albumin (BSA), lysozyme (LYS), and alfalfa leaf protein (ALF) by two large- and two medium-sized condensed tannin (CT) fractions of similar flavan-3-ol subunit composition is described. CT fractions isolated from white clover flowers and big trefoil leaves exhibited high-purity profiles by 1D/2D NMR and purities >90% (determined by thiolysis). At pH 6.5, large CTs with a mean degree of polymerization (mDP) of ∼18 exhibited similar protein precipitation behaviors and were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 55 publications
(108 reference statements)
2
58
0
Order By: Relevance
“…Some forage legumes like sainfoin and birdsfoot trefoil contain proanthocyanidins in all parts of the plant [14], while in alfalfa, perennial ryegrass and tall fescue ( Festuca arundinacea ) they accumulate mainly in the seed coat [15,16] and in white clover and red clover ( Trefolium pratense L.) mainly in the flowers [17,18]. However, trace concentrations of proanthocyanidin were detectable in areal parts of most temperate forages [19,20].…”
Section: Occurrence Of Proanthocyanidin In Temperate/prairie Foragesmentioning
confidence: 99%
See 4 more Smart Citations
“…Some forage legumes like sainfoin and birdsfoot trefoil contain proanthocyanidins in all parts of the plant [14], while in alfalfa, perennial ryegrass and tall fescue ( Festuca arundinacea ) they accumulate mainly in the seed coat [15,16] and in white clover and red clover ( Trefolium pratense L.) mainly in the flowers [17,18]. However, trace concentrations of proanthocyanidin were detectable in areal parts of most temperate forages [19,20].…”
Section: Occurrence Of Proanthocyanidin In Temperate/prairie Foragesmentioning
confidence: 99%
“…Ropiak et al [58] found that mDP of proanthocyanidin was the most important factor determining PCC, while monomer composition of proanthocyanidin was more important in explaining the interaction of proanthocyandin with protein in terms of hydrophobic binding and changing protein secondary structure. Several studies compared the PCC of proanthocyanidin fractions of different MW and all found that PCC increased with increasing mDP [17,59,60,61]. Habertson et al [62], however, suggested that mDP above eight would not further improve PCC effectiveness.…”
Section: Protein Precipitating Capacity As Affected By Proanthocyamentioning
confidence: 99%
See 3 more Smart Citations